Atropisomerism in the 2,3,4,5-Tetrahydro-1H-1,5-benzodiazepine Nucleus: Effects of Central Chirality at C3 on the N-Mesylation Reaction - Tabata, Hidetsugu; Tsuji, Yuka; Yoneda, Tetsuya; Tasaka, Tomohiko; Oshitari, Tetsuta; Takahashi, Hideyo; Natsugari, Hideaki (Synlett, 2018)
The mesylation reaction of the 1,3-dimethyl-2,3,4,5-tetrahydro-1H-1,5-benzodiazepine nucleus was investigated in detail. Two diastereomers (A and B) of 5-mesyl-1,3-dimethyl-2,3,4,5-tetrahydro-1H-1,5-benzodiazepines, originating from chirality at C3 and at the Ar–N(SO2) axis were formed, among which isomers of the derivative with a methyl group at C6 (R = CH3) were separable at room temperature. A and B had chair-like and boat-like conformations, respectively, in which the C3-methyl group adopts a pseudoequatorial arrangement. Furthermore, A and B were shown to be the thermodynamically and kinetically controlled products, respectively.
Keywords: benzodiazepines; mesylation; atropisomerism; conformation; chirality